GEOLOGICAL AND GEOCHEMICAL CHARACTERISTICS OF GRANITOIDS IN THE EASTERN TAURIDE BELT, SOUTHEASTERN TURKEY - Dumanlilar Ö.; Şen P.A.; Aydal D.; Dumanlilar H. (My University, 2006)
As a consequence of plate convergence and continental collision, widespread magmatism occurred in the Malatya-Elazig area of the eastern Tauride belt. Igneous activities in the study area can be subdivided into two separate phases, the Baskil and Bilaser Tepe complexes. The present study particularly focuses on these granitoid associations. The Late Cretaceous granitoid associations exhibit cale-alkaline and tholeiitic major-oxide trends. Baskil granitoids consist primarily of quartz, plagioclase, and hornblende, with relatively lesser amounts of orthoclase. Bilaser Tepe granitoids are mainly composed of quartz, orthoclase, plagioclase, hornblende, and biotite. Oxides and apatite are common accessory phenocrysts in both granitoids. Based on petrographic and bulk-rock geochemical data, Baskil granitoids are classified as quartz-diorite, quartz-monzodiorite, and tonalite, whereas Bilaser Tepe granitoids are granodiorite and tonalite. Both units have peraluminous and metaluminous compositions. Trace-element plots indicate that the Baskil granitoids have geochemical features similar to I-type granitoids derived from island-are settings. The Bilaser Tepe granitoids exhibit both I- and S-type characteristics, suggesting a post-collisional origin. Baskil magmatism is interpreted as arc magmatism related to Late Cretaceous convergence between the Keban microcontinent and the southern branch of Neo-tethys. This magmatic phase was followed by collision between the Keban microcontinent and the Bitlis-Pütürge massif. Continental collision resulted in crustal thickening. Subsequently, the Bilaser Tepe granitoids were intruded, signifying post-collisional tectonic setting in the Malatya-Elazig area. Consequently, the petrological and geochemical data are consistent with the geodynamic model of the eastern Taurus. Copyright © 2006 by V. H. Winston & Son, Inc. All rights reserved.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая